Dropout reduction management strategies in public high schools - Petilo, Roselyn Roxas (2006)
This study was undertaken to identify the common management strategies used by school heads and principals to reduce dropout rate among public schools in the Division of City Schools, Manila. A survey was conducted in fourteen randomly-selected public schools in the area of study. The traits of the principals, school size in terms of enrolment population, and school facilities served as the control variables while the dropout rate is the dependent variable. It was found that the development of a family atmosphere in school is the only factor that is directly related and significantly decreases the incidence of dropouts in public schools.